Assessment of subclinical cardiac dysfunction by speckle-tracking echocardiography among people living with human immunodeficiency virus - Liao, Chia-Te; Toh, Han Siong; Chang, Wei-Ting; Yang, Chun-Ting; Chen, Zhih-Cherng; Tang, Hung-Jen; Strong, Carol (Frontiers in Cardiovascular Medicine, 2023)
Background People living with HIV (PLWH) have an increased risk of developing cardiovascular diseases (CVD). As speckle-tracking echocardiography (STE) has been used to detect subclinical myocardial abnormalities, this study aims to detect early cardiac impairment among Asian PLWH using STE and to investigate the associated risk factors. Methods We consecutively recruited asymptomatic PLWH without previous CVD from a medical center of Taiwan, and their cardiac function was evaluated by conventional echocardiogram and STE. Enrolled PLWH were classified as antiretroviral therapy (ART)-experienced and ART-naive, and multivariable regressions were used to assess the association between myocardial strain and risk factors including traditional CVD and HIV-associated factors. Results A total of 181 PLWH (mean age: 36.4 ± 11.4 years, 173 males) were recruited and conventional echocardiogram parameters were within normal ranges. Decreased myocardial strain across the myocardium was found, with a mean left ventricular (LV) global longitudinal strain of −18.7 ± 2.9%. The LV strain in the ART-experienced group (−19.0 ± 2.9%) was significantly better than the ART-naive group (−17.9 ± 2.8%), despite a younger age and lesser CVD risk factors in the ART-naive group. Hypertension [B = 1.92, 95% confidence interval (95% CI) 0.19–3.62, p = 0.029] and ART-naive with both low and high viral loads (VL) (B = 1.09, 95% CI 0.03–2.16, p = 0.047; and B = 2.00, 95% CI, 0.22–3.79, p = 0.029) were significantly associated with reduced myocardial strain. Conclusion This is the first and largest cohort using STE to investigate myocardial strain in Asian PLWH. Our results suggest that hypertension and detectable VL are associated with impaired myocardial strain. Thus, timely ART administration with VL suppression and hypertension control are crucial in preventing CVD when making the management parallel with the improved life expectancy of PLWH on ART.